Enhancing Learning Outcomes through Discovery Learning: A Gender-Inclusive Approach in Secondary Education - Raman, Kumutha; Haidaa Umiera Hashim (WISE Pendidikan Indonesia, 2025)
The persistent gap in student achievement and gender participation in secondary education, particularly in rural contexts, highlights the need for inclusive pedagogical strategies that enhance both learning outcomes and equity. This study aimed to examine the effectiveness of discovery learning in improving academic performance and fostering gender-inclusive participation in science classes at a secondary school in Purwodadi, South Lampung, Indonesia. A classroom action research design was applied across two cycles involving 20 students (11 female and 9 male), with data collected through achievement tests, classroom observation sheets, and teacher reflection notes. Quantitative data were analyzed descriptively to measure mastery of learning outcomes, while qualitative data were thematically analyzed to capture participation dynamics. The findings indicate that student mastery improved from 65% in the first cycle to 95% in the second, while active participation among female students increased from 40% to 90%. These results confirm that discovery learning is not only effective in enhancing cognitive achievement but also serves as a gender-inclusive pedagogical framework that empowers female learners to engage actively in collaborative and inquiry-based learning. The implication of this study is that discovery learning can support teachers, curriculum designers, and policymakers in promoting equitable and high-quality education aligned with Sustainable Development Goal 4.